Industrial Opportunities and Challenges for Perovskite Photovoltaic Technology. Issue 9 (19th July 2019) - Wojciechowski, Konrad; Forgács, Dávid; Rivera, Thomas
Abstract : Perovskite solar cell technology is fast approaching its first commercial deployment, with the 10‐year mark since the first research having passed recently. Commercial entrance seems very tangible, but there are a number of remaining challenges related to various economic and technical factors. Conventional photovoltaic markets, such as utility scale photovoltaics, are quite rigid and very demanding for a new entrant. Perovskites offer several new value propositions, which offer monetization prospects in the near future, if properly used. In particular, functionalities such as flexibility, high specific power, and good low‐light performance enable new applications and broadening of the conventional PV usage. The specific cases of internet of things and building‐integrated photovoltaics are discussed, and market opportunities are analyzed. Technology incubation with simultaneous market presence in emerging applications can provide essential economic stability and time for the technology to develop into its full potential. Opportunities in high‐value markets and massive‐scale deployment are also addressed, with the analysis of potentially disruptive offerings being promised by perovskite photovoltaic technology. Abstract : Perovskite solar cell technology is in the advent of commercial entrance. These materials offer several new value propositions that can allow short‐term monetization in emerging applications, such as Internet‐of‐things or building‐integrated photovoltaics. Prospective offerings perovskite photovoltaics could deliver for high‐value markets, such as utility‐scale photovoltaics, and the feasibility of large deployments are also discussed.